Clinical Evaluation of Efficacy of Tc99m-Ethambutol in Tubercular Lesion Imaging. (17th August 2010) - Singh, Namrata; Bhatnagar, A.
Abstract : Purpose . The aim of this work was to develop specific radiopharmaceutical and to evaluate its efficacy in human to detect and locate the tubercular lesion. Materials and Methods . 99 m Tc -Ethambutol (EMB) was produced by direct labeling method. In vitro and in vivo biological studies and animal experiments were done. Phase I Clinical trial was performed. As per plan, 2 normal human subjects for biodistribution studies and fourteen patients (8 males and 6 females; age range of 25–50, with one patient aged 12 years as an exception) were chosen for clinical trial. Whole body scan and spots were acquired at 1 hour and 4 hour. Angiography, blood pool, and 24-hours spot images of the infected areas were also acquired. Result . Radiolabeling yielded> 85 % of labeled complex. In vitro and in vivo biological studies and animal experiments indicated 99 m Tc -EMB as a specific tuberculosis imaging agent. The biodistribution study in normal human subjects suggested stability of 99 m Tc -EMB, with main excretory pathways being renal and hepatobiliary, which appeared to be similar to the known behavior of unlabeled EMB. No adverse reactions were observed. 99 m Tc -EMB got localized in pulmonary and bone tubercular lesions. Scintigrams of 99 m Tc -EMB and 99 m Tc -Ciprofloxacin were compared at different time intervals. Conclusion . The present study states that developed 99 m Tc -EMB has high potential to qualify as a specific tuberculosis imaging radiopharmaceutical and is safe for human use.